The Impact of Sweet Potato Leaves Stew on Breast Milk Production in Postpartum Mothers at Bara-Barayya Public Health Center in Makassar - Sutrani Syarif; Nurasmi Nurasmi (USN Scientific Journal, 2020)
Breast milk is the most complete, safe, hygienic, and cheap nutritional food for babies. This research aimed to determine the impact of sweet potato (Ipomea Batatas) leaves stew towards breast milk production in postpartum mothers. The benefit of this research for postpartum mothers is to facilitate breastfeeding with herbal plants that are easily accessible. This type of research was a Quasi-experiment with a non-equivalent control group design. The number sample was 30 respondents. The sampling technique was the purposive sampling technique. Giving sweet potato leaves stew to postpartum mothers for seven days and measuring breast milk before and after providing the stew for seven days. The analysis used Independent T-test. The results showed an effect of giving sweet potato (Ipomea Batatas) leaves stew towards breast milk production in postpartum mothers with a value (sig 2-tailed = 0.000).